2003
DOI: 10.1029/2001gb001810
|View full text |Cite
|
Sign up to set email alerts
|

Four years' observations of terrestrial lipid class compounds in marine aerosols from the western North Pacific

Abstract: [1] In order to understand the long-range atmospheric transport of terrestrial organic matter over the open ocean, marine aerosol samples were collected on a biweekly basis from 1990 to 1993 in a remote island, Chichi-Jima, in the western North Pacific. The samples were analyzed for lipid class compounds using a capillary gas chromatography (GC) and GC/mass spectrometry (GC/MS). A homologous series of n-alkanes (C 20 -C 40 ), alcohols (C 13 -C 34 ), fatty acids (C 9 -C 34 ) and a,w-dicarboxylic acids (C 7 -C 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
216
2
4

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 239 publications
(249 citation statements)
references
References 45 publications
27
216
2
4
Order By: Relevance
“…Detected 40 organic acids totaled 82.6-756 ng/m 3 with an average value of 280 ng/m 3 , and accounted for 0.66%-3.69% of OC with an av- Saturated fatty acids (C14:0-C32:0) from this study in the PRD region showed a strong even carbon number predominance with a maximum at palmitic acid (C16:0) and stearic acid (C18:0) ( Table 1). This was quite similar to the distribution patterns reported in the urban areas (Fraser et al, 2002;Fu et al, 2010;Ho et al, 2011), but different from the bimodal distribution observed at the mountain site (Fu et al, 2008) or in marine aerosols (Fu et al, 2011;Kawamura et al, 2003) with maximums at C16:0 and C24:0/C28:0. The concentrations of C16:0 and C18:0 in the PRD region averaged 85.8 and 27.8 ng/m 3 , respectively, comparable with those reported in some urban sites, such as Nanjing in China (Wang and Kawamura, 2005) and Chennai in India (Fu et al, 2010).…”
Section: Levels and Compositionssupporting
confidence: 71%
“…Detected 40 organic acids totaled 82.6-756 ng/m 3 with an average value of 280 ng/m 3 , and accounted for 0.66%-3.69% of OC with an av- Saturated fatty acids (C14:0-C32:0) from this study in the PRD region showed a strong even carbon number predominance with a maximum at palmitic acid (C16:0) and stearic acid (C18:0) ( Table 1). This was quite similar to the distribution patterns reported in the urban areas (Fraser et al, 2002;Fu et al, 2010;Ho et al, 2011), but different from the bimodal distribution observed at the mountain site (Fu et al, 2008) or in marine aerosols (Fu et al, 2011;Kawamura et al, 2003) with maximums at C16:0 and C24:0/C28:0. The concentrations of C16:0 and C18:0 in the PRD region averaged 85.8 and 27.8 ng/m 3 , respectively, comparable with those reported in some urban sites, such as Nanjing in China (Wang and Kawamura, 2005) and Chennai in India (Fu et al, 2010).…”
Section: Levels and Compositionssupporting
confidence: 71%
“…An increase in wax concentrations in aerosol samples affected by wildfire plumes has been observed previously by Abas et al (1995), Conte and Weber (2002) and Kawamura et al (2003).…”
Section: Comparison Of Sugar With Plant Wax and Dehydroabietic Acid Dsupporting
confidence: 52%
“…Atmospheric particles contain organic tracers that are characteristic of their sources, mode of formation and subsequent alteration during transport downwind (Simoneit, 1977(Simoneit, , 1984(Simoneit, , 1989Marty and Saliot, 1982;Mazurek and Simoneit, 1984;Schauer et al, 1996;Fang et al, 1999;Simoneit et al, 1999;Conte and Weber, 2002;Kawamura et al, 2003;Simoneit et al, 2004a and references therein). Organic matter in aerosol particles is derived from four major sources and is admixed depending on environmental conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oleic acid has been detected in urban, rural, and marine aerosols and is used as a marker for meat cooking in continental aerosol. 12,[28][29][30][31][32][33][34][35][36] Several factors have motivated these studies, including: quantifying the time scale for organic aerosol to be converted from hydrophobic to hydrophilic via oxidation thereby influencing their CCN ability, estimating the lifetime of unsaturated organics in aerosol particles, and evaluating organic aerosol oxidation as a potential source of volatile organics. The reaction has been studied using pure oleic acid aerosols, [37][38][39][40][41][42][43][44][45] 2-30 nm thick films on polystyrene beads, 46 ∼1 µm thick films on aqueous sea salt aerosol 47 and on macroscopic films in coated wall flow tube studies.…”
Section: Introductionmentioning
confidence: 99%